Cultivo de microalgas em meios alternativos: extração de compostos bioativos de interesse à indústria de alimentos - Varandas, Roberta Conceição Ribeiro (2022)
Microalgae are photosynthetic microorganisms of great interest for biotechnological applications and especially in the food industry. Since they produce bioactive compounds such as proteins, carbohydrates, lipids, pigments, polysaccharides, among others. The present study aimed to extract bioactive compounds from microalgae biomass, seeking to reduce the costs of microalgae cultivation through the use of agro-industrial residues as alternative means as well as the large-scale cultivation of a microalgae to increase the production of compounds of interest. Eight species of microalgae were cultivated: Xanthonema sp.; Ankistrodesmus falcatus;Actinastrum hantzschii; Monoraphidium arcuatun; Spirulina maximum; Spirulina platensis;Scenedesmus ecornis;and Kirchneriella concorta in alternative media prepared from: hortifruti biocompost (BH), malt residue (RM), cassava starch (FE) and a mixture of hortifruti biocompost and malt residue (MIX ). And still barley malt residue and/or hortifruti biocompost substituting in different concentrations the synthetic médium. After the initial investigation of the most suitable alternative medium ratio for each microalgae performed with 250 mL flasks and observing the best growth through the growth curve comparing with the synthetic medium. Microalgae culture was carried out with pre-defined media on a laboratory scale to obtain biomass with 6L flasks containing 5 L of medium under controlled conditions to obtain biomass for analysis. The 8 species studied showed different growth responses in each of the tested media. The best responses were observed for Scenedesmus ecornis, with greater results for cultivation in the alternative medium with vegetable biocomposite at a concentration of 1%. Scenedesmus ecornis (D545BH) showed the highest biomass yield (583 mg.L-1) and highest productivity (41.6 mg.L-1) among all species.The most significant protein content was observed for Spirulina platensis grown in a medium with barley malt residue with 56.5 g 100g-1 . The highest levels of carbohydrates were found in Xanthonema sp. (D464WC) grown in MIX medium (38.8 g 100g-1).The highest lipid concentrations were observed in cultures of Actinastrum hantzschii (D467WC-BH) with 24 g 100g-1 and in Monoraphidium arcuatun (D459WC-RM) 25 g 100g-1 .Variations in ester compositions were observed in all species when cultivated in different media, although, in general, there were higher concentrations of polyunsaturated and monounsaturated esters. The species Xanthonema sp. (D464WC) grown in mix medium had the highest polysaccharide content (15%). Followed by the species Scenedesmus ecornis (D545WC), cultivated in BH medium, obtained 13.1% Phycocyanin levels were higher regardless of the extraction method for Spirulina platensis and there was no significant difference between the alternative and control medium. A Scenedesmus ecornis was cultivated in a photobioreactor with a capacity of 2,000L with the vegetable biocomposite medium and the cultivation proved to be efficient during the different growth phases. It allowed satisfactory cell growth during the phases. The highest protein contents were found during the stationary phase. The highest protein contents were found during the stationary phase. Different from the levels of carbohydrates and lipids, which were higher in the decline phase, when there was also a decrease in the nitrate and phosphate levels of culture. During the decline phase, there was also a greater production of mono- and polyunsaturated fatty acids and a greater accumulation of polysaccharide regardless of the type of extraction. There was still a greater accumulation of EPS during the same phase. The results of these scientific productions indicate that microalgae can be sources of compounds with important bioactive properties that have the potential to be used by the food industry. And yet Scenedesmus ecornis has the potential to be cultivated with hortifruti biocompost on a large scale and produced of interest.